Case report: Identification of facioscapulohumeral muscular dystrophy 1 in two siblings with normal phenotypic parents using optical genome mapping - Jiang, Jieni; Cai, Xiaotang; Qu, Haibo; Yao, Qiang; He, Tiantian; Yang, Mei; Zhou, Hui; Zhang, Xuemei (Frontiers in Neurology, 2024)
Objective: Facioscapulohumeral muscular dystrophy type 1 (FSHD1) is a relatively common form of autosomal-dominant muscular dystrophy characterized by variable disease penetrance due to shortened D4Z4-repeat units on 4q35. In this study, the genetic diagnosis of FSHD1 was confirmed using by optical genome mapping (OGM).Epigenetic heterogeneity was assessed based on methylation analysis.Methods: Whole-exome sequencing was performed with genomic-DNA samples from four members of the same family. OGM was used to identify D4Z4 structural variations and sodium bisulfite sequencing was utilized to investigate methylation levels of CpG sites in a region located distally to the D4Z4 array. A multidisciplinary team collected clinical data, and comprehensive family analyses were performed to assess phenotypes and genotypes.Results: Whole-exome sequencing did not reveal variants related to the patients' clinical phenotypes.OGM revealed that the proband was a compound heterozygote for the 4qA allele with four and eight D4Z4 repeats, whereas the affected younger brother had only one 4qA allele with four D4Z4 repeats.Both the proband and her younger brother had asymmetric weakness predominantly involving the facial, shoulder girdle, and upper arm muscles, whereas the younger brother had more severe clinical symptoms. The proband's father considered normal after a neurological examination, also carried the 4qA allele with eight D4Z4 repeats. The unaffected mother exhibited 49 D4Z4 repeats of the 4qA allele and a minor mosaic pattern with four D4Z4 repeats of the 4qA allele. Consequently, the presence of the 4qA allele in the four D4Z4 repeats strongly suggested involvement in maternal germline mosaicism. The CpG6 methylation levels were lower in symptomatic patients compared to those in the asymptomatic parents. The older sister had lower clinical scores and ACSS and higher CpG6 methylation levels than that of her younger brother.We used OGM to identify two siblings with FSHD1 with phenotypically normal parents. Our findings suggest that the 4qA allele of four D4Z4 repeats was inherited through maternal germline mosaicism. Their clinical phenotype heterogeneity was associated with the methylation 3 level. The results of this study provide valuable insights that can help in the molecular diagnosis of FSHD1 and understanding the clinical phenotypic variability.